Analisis Filogenetik Gen nosZ pada Bakteri Pseudomonas sebagai Denitrifikasi Nitrogen Berbahaya Berdasarkan Data Sekuens NCBI - Inayatul Izzati; Maulida Karima; Nayla Qoni’Atun Sholehah; Faturrahman; Sarkono (Journal of Microbiology, Biotechnology and Conservation, 2026)
The nosZ gene plays a crucial role in the reduction of nitrous oxide (N₂O) to dinitrogen (N₂), an environmentally benign form of nitrogen. However, the evolutionary diversity of this gene within the genus Pseudomonas has not been comprehensively investigated. This study aimed to analyze the phylogenetic relationships of the nosZ gene in Pseudomonas and to elucidate patterns of relatedness and clade differentiation associated with N₂O reduction capability within this bacterial group. Phylogenetic analysis was conducted using the Maximum Likelihood method based on nosZ nucleotide sequences obtained from the NCBI database. The results showed that the closest genetic relationships were observed among isolates belonging to the same species, including Pseudomonas lini (sp 18 and 19), P. brassicacearum (sp 6 and 7), P. grimontii (sp 16 and 17), and P. mandelii (sp 11 and 12), all of which exhibited a genetic distance of 0.00. This finding indicates a high level of sequence conservation, likely influenced by strong functional selective pressure and similar geographic origins. In contrast, the most distant genetic relationships were observed between P. mandelii (sp 11) and P. lini (sp 19) with a genetic distance of 0.5, as well as between P. brassicacearum and several other species with distances reaching up to 0.6. These results highlight significant evolutionary variation of the nosZ gene among Pseudomonas species.